Differences between phytosterols with different structures in regulating cholesterol synthesis, transport and metabolism in Caco-2 cells. (February 2020) - Yuan, Lanlan; Zhang, Fan; Jia, Shuo; Xie, Jianhua; Shen, Mingyue
Graphical abstract: Highlights: Phytosterols showed cholesterol-lowering effects in Caco-2 cells. Phytosterols mediating transporter – NPC1L1, ABCG5 and ABCG8. Phytosterols inhibit the synthesis by reducing HMGCS1 level. Phytosterols interrupt the conversion to cholesterol esters by lowering ACAT2 level. Structural differences have effects on cholesterol-lowering activity of phytosterols. Abstract: Phytosterols have been shown to be effective in reducing blood cholesterol by suppressing intestinal cholesterol absorption in both humans and animals. In present study, the inhibition of cholesterol absorption in Caco-2 cells by ergosterol, ergosterol acetate, β-sitosterol, stigmasterol, campesterol and stellasterol were systematically assessed. Results showed that the phytosterols produced cholesterol-lowering effect in Caco-2 cells. This effect was largely mediated via reducing the biosynthesis of cholesterol (HMGCS1); meditating the key proteins in cholesterol transportation and metabolism (NPC1L1, ABCG5/ABCG8); interrupting the conversion of cholesterol to cholesterol esters (ACAT2). Results indicated that their cholesterol-lowering activity may be correlated with the functional group (hydroxyl or ester) on C-3 position (ergosterol < ergosterol acetate) and the functional groups on C-5 position of phytosterols (ergosterol > stellasterol). Further researches are needed to confirm the cholesterol-lowering effects of phytosterols with functional group (methyl or ethyl) on C-24 and the functional groups on C-22 position.